First record of the Genus Lichnofugia from India with description of a new species (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini; Liarina) - Hajong, Sudhanya Ray (Zootaxa, 2014)
The genus Lichnofugia is reported for the first time from India with a description of Lichnofugia umshingensis sp. nov. from Shillong, Meghalaya. The distribution of Lichnofugia thus extends eastward from Peninsular Malaysia and Thailand to north- eastern India.